Clinical Characteristics and CD4+ T Cell Subsets in IgG4-Related Disease - Yang, Yan; Wang, Chen; Shi, Lei; Yang, Shuoran; Liu, Yan; Luo, Jing; Wang, Caihong (Frontiers in Immunology, 2022)
Objectives To characterize the clinical features of IgG4-related disease (IgG4-RD) and analyze the peripheral T lymphocyte subsets and cytokine levels. Methods A total of 52 patients with newly diagnosed IgG4-RD were enrolled in the retrospective study. Baseline clinical characteristics and examinational findings were systematically reviewed. Results IgG4-RD patients had a male predominance, with an average age of 57.4 ± 10.3 years (range 27-81). The mean number of involved organs was 2.7 (range 1-8). Submandibular gland (57.7%) and lacrimal gland/orbit (40.4%) were the most commonly involved organs. Serum IgG4 increased in 97.9% of the patients, the median level was 1300 (585.25, 1975) mg/dl. Decreased C3 and C4 accounted for 77.8% and 55.6% of this patient cohort, respectively. Receiver operating characteristic (ROC) test indicated the possibility of lung/pleura involvement when C3 was less than 0.570 g/l (AUC = 0.788, P = 0.014), and kidney involvement when C3 was less than 0.545 g/l (AUC = 0.796, P = 0.014). Compared with healthy controls (HC), the absolute Th1 counts were higher in IgG4-RD patients (157.58 cells/μl vs. 130.54 cells/μl, P = 0.038), while the absolute counts of Th2, Th17 and T regulatory (Treg) cells, as well as Th17/Treg ratio were not statistically different. The levels of serum IL-4, IL-6, IL-10, IL-17, TNF-α, and IFN-γ were higher in patients with IgG4-RD as compared with HC (P < 0.001). Serum IL-10 was positively correlated with IL-4, TNF-α and IFN-γ, but uncorrelated with Treg cells. Serum IgG4 level was positively associated with the number of affected organs, eosinophil counts, and ESR, whereas inversely associated with C3, C4, IgM, and IgA. Conclusion Submandibular and lacrimal glands are the most commonly involved organs in IgG4-RD. Serum C3 level could be a predictor of lung/pleura and kidney involvement in the disease process. Elevated Th1 cells are probably related to chronic inflammation and fibrosis. Treg cells are unlikely to play an important role in the pathogenesis of IgG4-RD.